2018
DOI: 10.1080/09712119.2018.1480487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substitution of Bermuda grass hay with Trichoderma fermented rice straw on growth, blood, and rumen fluid parameters in Barbados sheep

Abstract: The study was to ascertain the feasibility of using rice straw fermented by Trichoderma as ruminant roughage. Three species or three strains of Trichoderma (NTLg-Te S5-1, NTLg-Te S9-1, and Tien Chung Ca6-1) were used to inoculate hot water-sterilized rice straw. Result showed that rice straw fermented with Trichoderma NTLg-Te S5-1 had the highest cellulase and xylanase activity. Antioxidant ferulic acid content of water extract was improved after fermentation. Eighteen Barbados sheep were randomly distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, with the increasing awareness of environmental protection, agricultural wastes or by-products are required to be properly treated [ 2 , 3 , 4 ]. In order to effectively reduce animal production costs and increase the value of agricultural by-products, previous studies have suggested the use of by-products such as mushroom waste compost since it is rich in mycelium and contains abundant functional secondary metabolites, which can improve antioxidant capacities, and regulate inflammatory response as much as animal feed ingredients [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increasing awareness of environmental protection, agricultural wastes or by-products are required to be properly treated [ 2 , 3 , 4 ]. In order to effectively reduce animal production costs and increase the value of agricultural by-products, previous studies have suggested the use of by-products such as mushroom waste compost since it is rich in mycelium and contains abundant functional secondary metabolites, which can improve antioxidant capacities, and regulate inflammatory response as much as animal feed ingredients [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second category is the dietary fiber that cannot be digested by the animal itself [ 6 ]. A distinction can also be made between hard-to-digest fibers such as cellulose, chitin, and other fibers, depending on whether the microorganism can be digested [ 5 , 6 ]. However, high-fiber agricultural by-products may reduce the performance of monogastric animals in traditional concepts [ 6 ], so this proposal has not been favored by animal producers for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low moisture content of solid-state fermentation, filamentous fungi or yeasts are generally considered suitable for growth [97]. In addition, microorganisms such as yeast or Aspergillus oryzae, with high activities of carbohydrate catalyzing enzymes are also used to ferment high-fiber substrates, such as wheat bran, straw, and lupin flour [17,25,98]. The high-protein soybean meal is suitable for fermentation using microorganisms with high protease activity such as Lactobacillus spp.…”
Section: Solid-state and Liquid Fermentationsmentioning
confidence: 99%
“…Similarly, a Trichoderma spp. SSF also improved the NDF and ADF digestibility of rice straw in Barbados sheep compared to the unfermented rice straw [ 15 ]. Regarding to the modulation effects of a fungus, Antrodia cinnamomea was reported to reduce obesity via modulation of gut microbiota in mice fed high-fat diets [ 16 ].…”
Section: Introductionmentioning
confidence: 99%